2022
DOI: 10.3389/fphar.2022.1004888
|View full text |Cite
|
Sign up to set email alerts
|

Pinocembrin ameliorates atrial fibrillation susceptibility in rats with anxiety disorder induced by empty bottle stimulation

Abstract: Background: Anxiety disorder (AD) is the most common mental disorder, which is closely related to atrial fibrillation (AF) and is considered to be a trigger of AF. Pinocembrin has been demonstrated to perform a variety of neurological and cardiac protective effects through its anti-inflammatory and antioxidant activities. The current research aims to explore the antiarrhythmic effect of pinocembrin in anxiety disorder rats and its underlying mechanisms.Methods: 60 male Sprague-Dawley rats were distributed into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…We recently demonstrated that the high incidence of AF in AD rats is associated with cardiac autonomic nerve remodeling and electrical remodeling. 15 This was again confirmed in this study, with substantial changes in atrial electrophysiology, including abnormal prolongation of APD and shortening of ERP. AF can be maintained by re-entry and/or focal ectopic trigger.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…We recently demonstrated that the high incidence of AF in AD rats is associated with cardiac autonomic nerve remodeling and electrical remodeling. 15 This was again confirmed in this study, with substantial changes in atrial electrophysiology, including abnormal prolongation of APD and shortening of ERP. AF can be maintained by re-entry and/or focal ectopic trigger.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with previous studies, 15 a significant reduction in time-domain parameters, including average RR, SDRR, and RMSSD, was observed in AD rats compared with CTL rats (Figs. 3A-C).…”
Section: Inhibition Of Ampars Improved the Hrv In The Anxiety Disorde...supporting
confidence: 92%
See 3 more Smart Citations